Laser surfacing modification method for thermal barrier coating - LIU MIN; CHANG FA; TONG XIN; DENG CHANGGUANG; ZHOU KESONG; DAI MINGJIANG (2013)
The invention relates to a laser surfacing modification method for a thermal barrier coating. The method comprises the following steps of: firstly, carrying out washing and sand blasting on the surface of a base body; then, preparing the thermal barrier coating in a thermal spraying state on the surface of the base body; then, designing shape, size, arrangement rule and distribution density of laser modification unit bodies in a pile nail structure to be prepared in the thermal barrier coating; then, adjusting the process parameters of a laser according to a design model; then, performing laser modification to the thermal barrier coating; and finally, performing the stress relief annealing treatment to the laser modified thermal barrier coating. With the adoption of the method for arranging discontinuous and dispersed intensifying unit bodies in the pile nail structure in the thermal barrier coating, the thermal barrier coating can not only generate characteristic of soft and hard alternate change, but also g